Implementation of project-based learning (PjBL) model to increase students’ creativity and critical thinking skill in vocational creative product subjects - Lesman, Indra; Mulianti, Mulianti; Primawati, Primawati; Kassymova, Gulzhaina Kuralbayevna (Jurnal Pendidikan Teknologi Kejuruan, 2023)
The primary goal of education was the development of an individual's potential to foster intellectual, emotional, social, creative, and critical ways of thinking. It was important to remember that the concept and purpose of education can vary across cultures and contexts, and attitudes about education can also change over time as social, technological, and human developments occur. This research aimed to solve problems that arise in the classroom to improve students' creativity and critical thinking. This type of research used classroom action research that focuses on improving classroom learning in a practical manner pursued by a teacher by developing activities that can improve the quality of the learning process in the classroom. The data analysis results of the student product creativity assessment were 75% in the excellent creativity category and 25% at the excellent creativity level. Implementation of PjBL model had an effect on increasing student creativity as evidenced by the results of hypothesis testing, namely by testing with the Gain Score method, which there were N-gain results of 0.53 and showed a moderate increase in creativity compared to student scores before the implementation of the PjBL model, which there was an increase in the value before the model was implemented.